An education intervention to improve nursing students' understanding of medication safety. Issue 1 (January 2015) - Hewitt, Jayne; Tower, Marion; Latimer, Sharon
Abstract: Medication safety is a significant issue. Whilst medication administration is a routine task, it is a complex nursing activity. It is recognised in the literature that medication related adverse events are most often related to systems failures associated with the complex process of medication administration. This paper examines student's perceived effectiveness of an educational intervention, designed to demonstrate the complex and multidisciplinary factors of systems related failures in medication administration. The intervention was underpinned by adult and experiential learning concepts and used a problem-based learning approach. A series of short digital recordings were developed along with discussion points to illustrate multidisciplinary interactions involved in medication administration. A small sample of second and third year undergraduate nursing students ( n  = 28) evaluated the effectiveness of the educational resource. Our findings suggest that such resources are effective in demonstrating the complexity of medication related error and were authentic to practice. An educational intervention using problem based learning afforded nursing students the opportunity to engage with the systems factors that contribute to medication errors. Interventions that highlight these factors may play an important role in raising awareness of these issues and encourage students to carry this knowledge into clinical practice.